Remittances and Banking Sector Development in South Asia - Abdullah M Noman; Gazi S Uddin (The International Journal of Banking and Finance, 2011)
The paper investigates the interaction among foreign remittance, banking sector development and GDP in four South Asian nations that export huge pools of labour abroad. Multivariate Granger causality tests, based on error correction models, are employed with data spanning from 1976 to 2005. A key finding of the paper is that remittances and banking sector development influence per capita income in all four South Asian nations. In addition, interactions among the variables are also examined in a panel setting. As in individual country analyses, both remittance and banking sector development have positive and significant influences on the national income of South Asian countries. On the other hand, neither domestic products nor advancement in banking sector have significant impact on the remittance flows. This is new findings of the linkage between remittances and economic development, which may also be evident for countries exporting labour pools.